(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract: This research aims to determine the impact that financial illiteracy has caused in personal financial decisions, and to know the extent of awareness and understanding of individuals in all their categories of the financial literacy variable, especially in the various government banks sector, activities in the city of Baghdad, and this is done by identifying the impact of the dimensions of illiteracy. Financial represented by (financial knowledge, financial skills, financial position, financial well -being) in the dimensions of personal financial decisions represented by (financial planning, financial behavior, financial ability, investment, savings). The research sample was represented by individuals who are at the level of (employees, merchants, industrialists, individuals working in the agricultural sector, free business or housewives) and various frequencies, with a total of (240) individuals. The problem of research lies in the suffering of individuals from the weak financial awareness and the lack of awareness of the role that the financial laws play in its various dimensions in rationalizing the personal financial decision and contributing to reducing poverty and achieving economic growth. The importance of research in subjugating the concept of financial inclusion and personal financial decisions for field study in the banking sector is evident in an attempt to employ modern financial management methods to achieve sound financial decisions. The research followed the descriptive analytical approach, the questionnaire was used, the interviews in collecting data, and statistical means of (Alfacorpach laboratory, correlation coefficient, percentage, computational medium, standard deviation, difference factor, relative importance, multiple decline analysis depending on (Smartpls.4), (SPSSV.25). The research reached a number of results, the most important of which is: the existence of a fully literacy effect on personal financial decisions on the individual level. The results on the level of multiple impact showed that the most influential in the personal financial decisions of the financial literacy variable was (financial knowledge, financial position, financial well -being).